IDENTIFIKASI JENIS POHON HASIL ILLEGAL LOGGING DI KAWASAN TAMAN NASIONAL GUNUNG PALUNG - Nurul Ihsan Fawzi; Agus Novianto; Agus Supianto; Mahardika Putra Purba (Jurnal Hutan Tropis, 2021)
Deforestation makes a loss of 30.2% of the forest on Borneo from 1973 – 2010. Information about tree species has been logged still few. The aim of this study is to identify the types of trees that are sought and logged on Gunung Palung National Park. The method used was interviews with 45 loggers who had joined the UMKM program in collaboration between Yayasan ASRI, Health in Harmony, and Gunung Palung National Park Office. A field survey was conducted to find out the number of active loggers cutting down on Gunung Palung National Park. The result identified 15 families as tree species which mostly logged inside the park. Bengkirai (Shorea laevis Ridl.) and meranti (Shorea Roxb. Ex C.F.Gaertn.) are the most logged trees species. The frequency of logging can cut down a tree on average 10.6 trees per week or 533 trees a year for one logger. On 2018, the park already lost 34,286 trees from logging activity. The information about logged trees species is important for the conservation effort. Especially how to save species that are vulnerable and endangered.